GABAA receptor deficits predict recovery in patients with disorders of consciousness: A preliminary multimodal [11C]Flumazenil PET and fMRI study. Issue 10 (3rd July 2015) - Qin, Pengmin; Wu, Xuehai; Duncan, Niall W.; Bao, Weiqi; Tang, Weijun; Zhang, Zhengwei; Hu, Jin; Jin, Yi; Wu, Xing; Gao, Liang; Lu, Lu; Guan, Yihui; et al.
Abstract Objectives Disorders of consciousness (DoC)—that is, unresponsive wakefulness syndrome/vegetative state and minimally conscious state—are debilitating conditions for which no reliable markers of consciousness recovery have yet been identified. Evidence points to the GABAergic system being altered in DoC, making it a potential target as such a marker. Experimental design In our preliminary study, we used [11C]Flumazenil positron emission tomography to establish global GABAA receptor binding potential values and the local‐to‐global (LTG) ratio of these for specific regions. These values were then compared between DoC patients and healthy controls. In addition, they were correlated with behavioral improvements for the patients between the time of scanning and 3 months later. Functional magnetic resonance imaging resting‐state functional connectivity was also calculated and the same comparisons made. Principal observations lobal GABAA receptor binding was reduced in DoC, as was the LTG ratio in specifically the supragenual anterior cingulate. Both of these measures correlated with behavioral improvement after 3 months. In contrast to these measures of GABAA receptor binding, functional connectivity did not correlate with behavioral improvement. Conclusions Our preliminary findings point toward GABAA receptor binding being a marker of consciousness recovery in DoC. Hum Brain Mapp 36:3867–3877, 2015. © 2015 Wiley Periodicals, Inc.